Role of Circulating Tumor Cells in Determining Prognosis in Metastatic Breast Cancer - Dhaka, Sonia; Tripathi, Rupal; Doval, Dinesh Chandra; Mehta, Anurag; Maheshwari, Udip; Koyyala, Venkata Pradeep Babu; Singh, Jatinderpal (South Asian Journal of Cancer, 2022)
Background Circulating tumor cells (CTCs) in the peripheral blood may play a major role in the metastatic spread of breast cancer. This study was conducted to assess the role of CTCs to determine the prognosis in terms of survival in metastatic breast cancer patients.Methods This prospective study of 36 patients was conducted at the Hospital from April 2016 to May 2018. Details of each patient related to the demographic profile, tumor type, treatment, and follow-up information were recorded. The number of CTCs in the peripheral blood was measured by Celsee PREP 400 sample processing system and Celsee Analyzer imaging station.Results There was a positive correlation between the number of site of metastasis with number of CTCs (p-value < 0.001). In the patients with clinical/partial response, a significant reduction in the number of CTCs after 1 month of therapy was observed (p-value = 0.003). When the number of CTCs at baseline and 6 months were compared with the positron emission tomography response at 6 months, a statistically significant difference in CTCs in patients having partial response after 6 months was observed (p-value = 0.001). On comparison with the responder groups, a statistically significant reduction in CTCs at baseline and 6 months was observed (p-value = 0.001). Patients with CTCs less than 5 and more than or equal to 5 after 1 month of treatment had a mean progression-free survival of 11.1 months and 7.5 months (p-value = 0.04) and a mean overall survival of 11.6 and 9.6 months (p-value = 0.08), respectively.Conclusion Assessment of CTCs provides a more quantifiable response than radiographic evaluation and at a much earlier time point and is also a better predictor of survival.
Keywords: circulating tumor cells; metastatic breast cancer; response; survival; prognosis